Epistemologies of the South, Mozambique and a post-colonial feminist quest / Epistemologías del Sur, Mozambique y una búsqueda feminista postcolonial - CUNHA, Teresa (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Far beyond Simone’s warnings, the epistemologies of the South are a theoretical body that allows us to think, in a critically different way, about the construction, not only social but also potentially colonial, of the concept of ‘woman’ and therefore, the emancipation of women. This article has a double goal. Firstly, it is to question feminisms through the concepts of the abyssal line and of ‘subaltern, insurgent cosmopolitanism’. The second is to analyse an episode of misogynistic emergency which occurred in Mozambique in 2016 and the resistance and feminist solidarity that followed by exerting a post-colonial feminist imagination. My methodological approach is based on the analysis of women’s narratives obtained in interviews, journalism pieces and social networks. RESUMEN Más allá de las advertencias de Simone, las epistemologías del Sur son un problema que nos permite pensar, de manera críticamente diferente, acerca de la construcción, no solo social sino también potencialmente colonial, del concepto de "mujer" y, por lo tanto, de la emancipación de mujer. Este artículo tiene un doble objetivo. En primer lugar, cuestionar el feminismo a través de los conceptos de la línea abismal y del "cosmopolitismo subalterno e insurgente". En segundo lugar, analizar un episodio de emergencia misógina que ocurrió en Mozambique en 2016 y la resistencia y solidaridad feminista que siguió al ejercer una imaginación feminista poscolonial. Mi enfoque metodológico se basa en el análisis de las narrativas de mujeres obtenidas en entrevistas, artículos de periodismo y redes sociales.